2010
DOI: 10.1164/rccm.200810-1658oc
|View full text |Cite
|
Sign up to set email alerts
|

Increased Propensity for Central Apnea in Patients with Obstructive Sleep Apnea

Abstract: Rationale: There is increasing evidence of increased ventilatory instability in patients with obstructive sleep apnea (OSA), but previous investigations have not studied whether the hypocapnic apneic threshold is altered in this group. Objectives: To compare the apneic threshold, CO 2 reserve, and controller gain between subjects with and without OSA matched for age, sex, and body mass index. Methods: Hypocapnia was induced via nasal mechanical ventilation for 3 minutes. Cessation of mechanical ventilation res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
114
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(119 citation statements)
references
References 32 publications
3
114
2
Order By: Relevance
“…15 Second, CPAP serves to stabilize the upper airway, which would be predicted to increase controller gain in these patients. 15,16 Chemoresponsiveness, defi ned as the body's ventilatory response to CO 2 plus the ability to respond to chemical stimuli (an open airway), would increase with CPAP-induced patency of the upper airway. 17 Thus, central apnea may occur due to CPAP-induced hypocapnia.…”
mentioning
confidence: 99%
“…15 Second, CPAP serves to stabilize the upper airway, which would be predicted to increase controller gain in these patients. 15,16 Chemoresponsiveness, defi ned as the body's ventilatory response to CO 2 plus the ability to respond to chemical stimuli (an open airway), would increase with CPAP-induced patency of the upper airway. 17 Thus, central apnea may occur due to CPAP-induced hypocapnia.…”
mentioning
confidence: 99%
“…However, we note that 1 month is considered sufficient to normalize the effects of sleep apnea on loop gain (13,14). Hence, available evidence suggests that at 1 month it is reasonable to reconsider the use of alternative strategies with a greater scope for resolving ventilatory instability (e.g., ASV) (18).…”
Section: Respondersmentioning
confidence: 91%
“…In patients with heart failure, CPAP reduces residual CSAs over time (12), indicating that loop gain is gradually reduced with ongoing treatment. In patients with OSA without heart failure, the ventilatory chemoreflex response to CO 2 (a key component of ventilatory stability) is normalized with approximately 4 weeks of CPAP treatment (13,14).…”
mentioning
confidence: 99%
“…It remains unclear to what extent sleep impairment is the cause or the effect of CompSAS (24). It was suggested that an elevated nasal resistance might relate to frequent arousals, which could presumably contribute to an increase in central apneas (25).  All these pathophysiological issues may be clinically important, since they can potentially affect treatment approaches, keeping in mind that patients developing CSA after OSAS treatment seem to have a poorer prognosis as compared to those only affected by OSAS, eventually also because of low CPAP compliance.…”
Section: Editorialmentioning
confidence: 99%